The Effects Of Compensation On Job Satisfaction And Turnover Intention - Burhanudin Burhanudin; Fajar Ardiansyah; Ferri Kuswantoro (CV. AFDIFAL MAJU BERKAH, 2025)
One of the problems faced by PT. Telkom Akses Yogyakarta has a fairly high employee turnover intention. The causes of turnover intention include compensation and job satisfaction, which are still relatively low. Therefore, the objectives of this study are to: (1) test the effect of compensation on turnover intention; (2) test the effect of compensation on job satisfaction; and (3) test the effect of job satisfaction on turnover intention. The sample in this study was 94 employees of PT. Telkom Access Yogyakarta. The data collection technique used a questionnaire, while the data analysis technique used path analysis with the AMOS program. The results of the study found that compensation had a negative and insignificant effect on turnover intention. This can be interpreted that the higher the compensation, the lower the employee's intention to leave, although the effect is not too strong. Compensation has a positive and significant effect on job satisfaction. This means that the higher the compensation, the higher the employee's job satisfaction. Job satisfaction has a negative and insignificant effect on turnover intention. This means that the higher the job satisfaction, the lower the employee's intention to leave, although the effect is not too strong.